(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
The festival of classical performances organised by Inda (Istituto Nazionale del Dramma Antico) in Siracusa since 1914 is unique in the Italian theatre scene. The essay focuses on the peculiar composition of the audience of the event: does the horizon of expectation influence the decisions of the artistic directorship? What are the effects and the consequences of such a complex phenomenon on the works represented?